Posterior Reversible Encephalopathy Syndrome in a Patient With Microscopic Polyangiitis: A Case Report and Literature Review - Xu, Jing; Ding, Ying; Qu, Zhen; Yu, Feng (Frontiers in Medicine, 2021)
Central nervous system (CNS) is rarely involved in microscopic polyangiitis (MPA). Here, we report a 14-year-old girl with MPA who developed new-onset seizures with deterioration of renal function. Her brain CT scan and MRI showed concurrent complications of intracerebral hemorrhage and posterior reversible encephalopathy syndrome (PRES). She got remission with combinations of methylprednisolone pulse, plasma exchange, regular hemodialysis, antiseizure and antihypertension medications. Furthermore, it is crucial to exclude the adverse effect of medications such as corticosteroid and biological therapy. We searched the literatures, retrieved 6 cases of MPA with PRES and summarized their clinical characteristics.